A roadmap to engaging patients in research: The experience of a large academic research hospital in Canada - Rabia Zaheer; Sara Morassaei; Sander Hitzig; Laurie Legere; Mary Jane Torrie; Lisa Di Prospero (The Beryl Institute, 2023)
Recent definitions of patient engagement in research (PER) emphasize that engagement should be meaningful, active and an equal collaboration across the research continuum. The increased interest in patient engagement is predicated on the recognition by researchers of the unique experiential knowledge provided by individuals with lived experience, ethical obligations to democratize science and that patient involvement can potentially lead to improved outcomes for patients and researchers. Sunnybrook Health Sciences Center is a large academic research hospital in Toronto, Canada which aimed to create clearer pathways for patients to have a more prominent voice in the development, implementation, and dissemination of research. However, to ensure that the policies, practices and resources to support PER would be viewed as meaningful to all stakeholders (including, but not limited to, administrators, clinicians, clinician researchers, scientists, patients, family members and caregivers), a series of structured activities were undertaken to foster collective buy-in and co-create an operational implementation plan for PER. The activities consisted of a consecutive mixed methods approach of three phases of discovery: a survey, focus groups and interviews, and an in-person town hall. We describe our approach to implementation and operationalization of PER at an academic hospital based on five identified priority themes: education and training, partnerships, matching programs, policies and measures. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.